Staphylococcus aureus Strains With a Negative Coagulase Tube Test are Associated With Staphylocoagulase Genotypes - Carly L. Botheras; Dieter Bulach; Eugene Athan (Frontiers in Bioscience-Scholar, 2025)
Background: Staphylococcus aureus is a significant human pathogen. Therefore, differentiating Staphylococcus aureus (S. aureus) from coagulase-negative staphylococcal species is an important step in the diagnostics procedure. The coagulase tube test assay is used as a preliminary identification test; however, there are instances of S. aureus isolates testing negative. We hypothesized that this might affect clinical outcomes and that particular staphylocoagulase genotypes are not detected by the coagulase tube test. Methods: In total, 122 clinical bloodstream S. aureus isolates with clinical metadata were examined for coagulating ability. The coa genotype was determined for each isolate using whole genome sequencing, and regions flanking the coa gene in the genome sequence were examined for synteny to identify differences that may indicate possible differences in coa gene regulation. In addition, a subset of isolates was assessed for coa gene expression using reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR). Results: All 122 isolates were found to have the coa gene, and all but one tested positive in the coagulase slide test. Comparatively, 18.9% of the isolates tested negative in the coagulase tube test assay. There was no association between an isolate having a negative tube test and having a complicated bloodstream infection. Among the 122 isolates, 11 coa genotypes were present, with similarities between the coa gene and comparative genome phylogenies and grouping of multilocus sequence types (MLST, abbreviated to ST), indicating that the coa gene may be vertically inherited. Staphylocoagulase type X and XI isolates were more likely to test negative in the coagulase tube test despite evidence of an intact functional coa gene. Conclusions: The S. aureus lineages may be negative in the coagulase tube test, especially ST15 and ST3911 (from staphylocoagulase genotype X). Our analysis suggests that the observed negativity in the coagulase tube test is due to the inability of particular coagulase types to coagulate the substrate provided in the commercial test. This has implications for using the tube test in differentiating Staphylococcus aureus isolates from other species. The Illumina genome sequencing read-set for each isolate was submitted to the National Center for Biotechnology Information (NCBI) under the accession number PRJNA611667.